2013
DOI: 10.2298/vsp1301086p
|View full text |Cite
|
Sign up to set email alerts
|

Cervical cancer screening in Serbia

Abstract: nem

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…According to the World Bank, economies can be divided into low income (LI), lower‐middle income (LMI), upper‐middle income (UMI), and high income (HI) in relation to GNI per capita (Figure ). In this study, the 53 WHO ER Countries were thus divided into: LMI, $1026‐4035 (Armenia, Georgia, Kyrgyzstan, Moldova, Tajikistan, Ukraine, and Uzbekistan); UMI, $4036‐12 475 (Albania, Azerbaijan, Belarus, Bosnia and Herzegovina, Bulgaria, Kazakhstan, FYR of Macedonia [FM], Hungary, Montenegro, Romania, Serbia, Turkey, and Turkmenistan); and HI, $12 476 (Austria, Belgium, Czech Republic, Denmark, Estonia, Finland, France, Germany, Greece, Iceland, Ireland, Israel, Italy, Luxembourg, Norway, Poland, Portugal, Slovakia Republic, Slovenia, Spain, Sweden, Switzerland, the Netherlands, and the United Kingdom, Andorra, Croatia, Cyprus, Malta, Monaco, Latvia, Lithuania, Russian Federation, and San Marino) (World Bank and Lending Groups 2016) (Table ) …”
Section: Methodsmentioning
confidence: 99%
“…According to the World Bank, economies can be divided into low income (LI), lower‐middle income (LMI), upper‐middle income (UMI), and high income (HI) in relation to GNI per capita (Figure ). In this study, the 53 WHO ER Countries were thus divided into: LMI, $1026‐4035 (Armenia, Georgia, Kyrgyzstan, Moldova, Tajikistan, Ukraine, and Uzbekistan); UMI, $4036‐12 475 (Albania, Azerbaijan, Belarus, Bosnia and Herzegovina, Bulgaria, Kazakhstan, FYR of Macedonia [FM], Hungary, Montenegro, Romania, Serbia, Turkey, and Turkmenistan); and HI, $12 476 (Austria, Belgium, Czech Republic, Denmark, Estonia, Finland, France, Germany, Greece, Iceland, Ireland, Israel, Italy, Luxembourg, Norway, Poland, Portugal, Slovakia Republic, Slovenia, Spain, Sweden, Switzerland, the Netherlands, and the United Kingdom, Andorra, Croatia, Cyprus, Malta, Monaco, Latvia, Lithuania, Russian Federation, and San Marino) (World Bank and Lending Groups 2016) (Table ) …”
Section: Methodsmentioning
confidence: 99%
“…Also, they have shown that the Pap smear use as the primary test, and well organized screening program at the national level could play an important role. These measures could have a major effect on decline in cervical cancer incidence and mortality in the next few decades by detecting and treating precancerous lesions [37][38][39][40][41] . The implementation of organized screening program in Serbia started in December 2012 (in Belgrade at Voždovac, Palilula and Čukarica), but we still are dealing with obstacles, such as low percent of women of target population who have been screened within the program 42,43 .…”
Section: Discussionmentioning
confidence: 99%
“…Cervical cancer in Serbia is the fourth leading cancer among women and the second most common cancer among women aged 15-44 [3]. Many efforts have been made to decrease the incidence of cervical cancer, including organized cervical cancer screenings for all women aged 25 to 69, and the availability of vaccination for HPV [4]. Around threequarters of all cases of cervical cancer, along with a significant proportion of all cases of anal, vulva, vaginal, penile, and cancer of oropharynx, are associated with an HPV infection with types 16 and 18, which are part of all HPV vaccines.…”
Section: Introductionmentioning
confidence: 99%